PENERAPAN METODE BERCERITA DALAM BIDANG PERKEMBANGAN SOSIAL EMOSIONAL ANAK DI RA MUSLIMAT NU 15 MALANG - Nurul Izza Husain; Khoirul Asfiyak; Ika Anggraheni (UNISMA, 2022)
Education is one of the most important parts in human life. According to UU No 20 tahun 2003 education is a conscious and planned effort to realize the moment of learning and the process to enable student to actively develop their potential to have spiritual powers, self-control, individuality, intellect, chastity, and the skill that required of them, of society, of nations and countries. Raudhatul Athfal is one of the young education 4-6 year which is recognized and equaled to the kindergarden. The development of children at ayoung age is a crucial period and needs to be treated as early as possible to give a child’s ability to develop optimally according to aspects of child development. From the background of research on the issue of this research is the application of the telling method and how the emotional social development of the kid RA Muslimat NU 15 Malang. The objective of this research was to describe the appliocation of a method to tell the kids about the emotional social development of the RA Muslimat NU 15 Malang. The type of research is qualitative descriptive. The technique used in collecting data was the author conducting a series of observation, interview, and documenting activities to the research site of RoudatulAthfal RA Muslimat NU 15 Malang. The child’s emotional social development based on observation children can conclude that class B3 as a whole is still in infancy that’s a total of 782 or 48.875. The number of kids in class B3 are 16, kids with really good criteria is 0 by 0% percentage, then the child with the criteria developed as expected amounts to 4 at 25%, and the child with the starting criteria is 12 at 75%, and the child with the undeveloped criteria is 0 at 0%.